Solid waste graphite-based base charged adsorbent and preparation method and application thereof in air carbon capture
By pretreating solid waste graphite and gradient oxidation treatment, combined with electrochemical activation, solid waste graphite base charged adsorbent is prepared, which solves the problems of high cost, high energy consumption and low efficiency of existing adsorbents, and achieves low cost and efficient CO2 capture and excellent cycling performance.
Patent Information
- Application Number
- CN202510313888.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-03-17
AI Technical Summary
The existing adsorbents have high costs, large regeneration energy consumption, and low adsorption efficiency in low concentration CO2 in direct air carbon capture (DAC). The acquisition cost of traditional graphite materials is high, and the purification process is high pollution and energy consumption.
Solid waste graphite is used as raw material, and a porous structure is formed through pretreatment steps such as pickling, puffing, and ball milling. Then it is mixed with CaCO3 and oxidized in a gradient manner, combined with electrochemical activation, and embedded in OH- to prepare a solid waste graphite base charged adsorbent.
It greatly reduces the cost of raw materials, increases the specific surface area and adsorption capacity of the adsorbent, reduces the regeneration temperature and energy consumption, and achieves efficient CO2 capture and excellent cycle stability.
Smart Images

Figure CN119909651A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adsorbents, and in particular relates to a solid waste graphite-based alkaline charged adsorbent, a preparation method thereof, and an application thereof in air carbon capture. Background Art
[0002] Direct air carbon capture (DAC) technology is a key negative emission technology to address climate change, but existing adsorbents face problems such as high cost, high regeneration energy consumption, and low low-concentration CO2 adsorption efficiency. Current mainstream technologies include: Liquid adsorption technology (such as alkaline solution, amine solution): high temperature regeneration (>120°C) is required, energy consumption is high (2.5-3.5GJ / tCO2) and equipment is prone to corrosion. Solid amine adsorbent: relies on organic amine functionalization (such as polyethyleneimine), but amine groups are prone to clogging pores, resulting in increased mass transfer resistance and significant amine volatilization losses.
[0003] Metal-organic frameworks (MOFs): Although they have high adsorption capacity, they are expensive to synthesize (>$1000 / kg) and have poor stability.
[0004] The rise of charged adsorption technology provides a new path to break through the above bottlenecks. This technology uses the acid-base neutralization reaction of CO2 and hydroxyl ions to capture CO2 by electrochemically regulating the surface charge state of the adsorbent. A new type of graphite-based charged adsorbent is introduced for capturing carbon dioxide directly from the air. The material embeds hydroxide ions into the pores of low-cost activated carbon through electrochemical charging to form chemical adsorption sites, which can efficiently capture CO2 and generate carbonates at room temperature. Compared with traditional methods, its regeneration temperature is significantly reduced (90-100℃), and it supports Joule heating, requiring only renewable energy for power supply. Experiments show that the material has a CO2 adsorption capacity of 0.26mmol / g at low pressure, stable performance after 150 cycles, and has antioxidant properties. In real environment tests, the CO2 concentration was reduced from 500ppm to 25ppm within 25 minutes. This technology has the advantages of low cost, controllability and conductivity, and provides a new direction for low-carbon DAC processes. However, the graphite-based adsorbent has the following problems: traditional graphite materials require high-purity raw materials, and the cost of obtaining raw materials is high. At the same time, the purification of natural graphite has the problem of high pollution and high energy consumption. For example, the graphite resources contained in waste lithium-ion batteries have great application potential and extremely broad application prospects in the fields of new energy and electronics industry. Therefore, it is urgent to recycle negative electrode graphite materials into porous charged adsorbents. In addition, the existing traditional adsorbents do not combine electrochemical activation and gradient pore design, so the adsorption capacity is low and the desorption energy consumption is still high. Summary of the invention
[0005] In view of the above-mentioned prior art, the present invention provides a solid waste graphite-based alkaline charged adsorbent and a preparation method thereof and application in air carbon capture, which solves the problems of high cost and low efficiency of the prior art.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a solid waste graphite-based alkaline charged adsorbent, comprising the following steps:
[0007] S1: acid-washing the solid waste graphite, then placing the acid-washed solid waste graphite in an inert gas atmosphere, keeping it at 750-850° C. for 2-3 hours, and grinding it into powder with a particle size of ≤50 μm after the end of the insulation, to obtain pretreated solid waste graphite;
[0008] S2: Mix the pretreated solid waste graphite and CaCO3, add H2O2 and stir evenly to obtain a composite slurry;
[0009] S3: molding the composite slurry into a film of 0.2-0.3 mm, and drying the film in vacuum at 100° C. for 24 h, and then cutting the film into graphite electrode sheets;
[0010] S4: In KOH electrolyte, use graphite electrode as working electrode, Pt as counter electrode, SCE as reference electrode, and keep it at 2V for 2h to obtain solid waste graphite-based alkaline charged adsorbent.
[0011] The beneficial effects of the present invention are as follows: the method provided by the present invention uses solid waste graphite as raw material, greatly reducing the cost of raw materials, and then pre-treating the solid waste graphite (pickling, puffing and ball milling), pickling removes impurities on the surface of the solid waste graphite, puffing makes the graphite form a porous or loose structure, ball milling reduces the size of graphite particles and optimizes the morphology, and then the graphite is mixed with CaCO3, and then H2O2 is added for gradient oxidation etching to obtain a gradient pore distribution of macropores-mesopores-micropores, thereby increasing the specific surface area, and then electrochemically activated, OH is filled - , and a solid waste graphite-based alkaline charged adsorbent is obtained.
[0012] Based on the above technical solution, the present invention can also be improved as follows.
[0013] Furthermore, the pickling is performed by soaking the solid waste graphite in 20% hydrochloric acid for 10 to 20 minutes.
[0014] Further, the grinding is to ball-mill the solid waste graphite at a rotation speed of 300 to 500 r / min.
[0015] The beneficial effect of adopting the further technical solution is that the pretreated graphite has less impurities, smaller particle size and better morphology and structure.
[0016] Furthermore, the mass ratio of pretreated solid waste graphite and CaCO3 is 1:2-5.
[0017] Further, the material ratio of the mixture of pretreated solid waste graphite and CaCO3 to H2O2 is 1g:1~3mL.
[0018] The beneficial effect of adopting the further technical solution is that the obtained solid waste graphite-based alkaline charged adsorbent can have a reasonable gradient pore distribution, and can embed more OH - .
[0019] Furthermore, the electrolyte is a KOH solution or a NaHCO3 solution.
[0020] Furthermore, the charging was performed at a constant voltage of 2 V for 2 h or at a pulse charging of 0.5 V at intervals of 10 min for 2 h.
[0021] The beneficial effect of adopting a further technical solution is: by electrochemical means, OH is embedded on the surface of the gradient pores. - , which greatly improves the performance of the final solid waste graphite-based alkaline charged adsorbent.
[0022] The present invention also provides a solid waste graphite-based alkaline charged adsorbent prepared by a preparation method of the solid waste graphite-based alkaline charged adsorbent.
[0023] The present invention also provides the use of solid waste graphite-based alkaline charged adsorbent in air carbon capture.
[0024] The beneficial effects of the present invention are as follows: the solid waste graphite-based alkaline charged adsorbent provided by the present invention reuses solid waste graphite, and the coordinated design of gradient pores and electrochemical activation allows the adsorbent to obtain excellent performance. In a low CO2 concentration environment, the dynamic adsorption capacity reaches 3.2 mmol / g, the adsorption amount in a high humidity environment only decreases slightly, the electrochemical desorption energy consumption is 0.6 GJ / t CO2, the CO2 desorption rate is >95%, and the capacity retention rate after 100 cycles is about 95%. Its excellent performance allows it to be used on a large scale on DAC, so the solid waste graphite-based alkaline charged adsorbent has excellent industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM image of the solid waste graphite in Example 1;
[0026] Figure 2 This is a macroporous SEM image of the solid waste graphite-based alkaline charged adsorbent prepared in Example 1;
[0027] Figure 3 This is a mesoporous SEM image of the solid waste graphite-based alkaline charged adsorbent prepared in Example 1;
[0028] Figure 4 This is a micropore SEM image of the solid waste graphite-based alkaline charged adsorbent prepared in Example 1;
[0029] Figure 5 It is the flow chart of adsorption-regeneration cycle;
[0030] Figure 6 It is a statistical diagram of adsorption performance;
[0031] Figure 7 The cycle performance diagram is shown in Figure 2. DETAILED DESCRIPTION
[0032] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0033] Example 1
[0034] A solid waste graphite-based alkaline charged adsorbent, the preparation method of which comprises the following steps:
[0035] S1: immerse the solid waste graphite in 6M HCl, stir at 60°C for 2h, then wash the acid-washed solid waste graphite with deionized water until it is neutral, place it in a nitrogen atmosphere, and keep it at 800°C for 2.5h. After the insulation, grind it into powder with a particle size of ≤50μm to obtain pretreated solid waste graphite;
[0036] S2: pretreated solid waste graphite and CaCO3 are mixed in a mass ratio of 1:3, and H2O2 is added and stirred evenly (the material ratio of the mixture of pretreated solid waste graphite and CaCO3 to H2O2 is 1g:2mL) to obtain a composite slurry;
[0037] S3: molding the composite slurry into a 0.25 mm film, and drying the film in vacuum at 100° C. for 24 h, and then cutting the film into graphite electrode sheets;
[0038] S4: In 1M KOH electrolyte, use graphite electrode as working electrode, Pt as counter electrode, SCE as reference electrode, and charge at constant voltage of 2V for 2h to obtain solid waste graphite-based alkaline charged adsorbent.
[0039] Example 2
[0040] A method for preparing a solid waste graphite-based alkaline charged adsorbent comprises the following steps:
[0041] S1: immerse the solid waste graphite in 6M HCl, stir at 60°C for 2h, then wash the acid-washed solid waste graphite with deionized water until it is neutral, place it in a nitrogen atmosphere, and keep it at 750°C for 3h. After the insulation, grind it into powder with a particle size of ≤50μm to obtain pretreated solid waste graphite;
[0042] S2: pretreated solid waste graphite and CaCO3 are mixed in a mass ratio of 1:2, and H2O2 is added and stirred evenly (the material ratio of the mixture of pretreated solid waste graphite and CaCO3 to H2O2 is 1g:1mL) to obtain a composite slurry;
[0043] S3: molding the composite slurry into a 0.2 mm film, and drying the film in vacuum at 100° C. for 24 h, and then cutting the film into graphite electrode sheets;
[0044] S4: In 1M NaHCO3 electrolyte, use graphite electrode as working electrode, Pt as counter electrode, SCE as reference electrode, and pulse charge at a voltage of 0.5V and an interval of 10min for 2h to obtain solid waste graphite-based alkaline charged adsorbent.
[0045] Example 3
[0046] A solid waste graphite-based alkaline charged adsorbent, the preparation method of which comprises the following steps:
[0047] S1: immerse the solid waste graphite in 6M HCl, stir at 60°C for 2h, then wash the acid-washed solid waste graphite with deionized water until it is neutral, place it in a nitrogen atmosphere, and keep it at 850°C for 2h. After the insulation, grind it into powder with a particle size of ≤50μm to obtain pretreated solid waste graphite;
[0048] S2: pretreated solid waste graphite and CaCO3 are mixed in a mass ratio of 1:5, and then H2O2 is added and stirred evenly (the material ratio of the mixture of pretreated solid waste graphite and CaCO3 to H2O2 is 1g:3mL) to obtain a composite slurry;
[0049] S3: molding the composite slurry into a 0.3 mm film, and drying the film in vacuum at 100° C. for 24 h, and then cutting the film into graphite electrode sheets;
[0050] S4: In 1M KOH electrolyte, use graphite electrode as working electrode, Pt as counter electrode, SCE as reference electrode, and charge at constant voltage of 2V for 2h to obtain solid waste graphite-based alkaline charged adsorbent.
[0051] Comparative Example 1
[0052] A graphite-based alkaline charged adsorbent, the preparation method of which comprises the following steps:
[0053] S1: immerse commercial high-purity graphite powder in 6M HCl solution, stir at 60°C for 2h, then wash the acid-washed graphite powder with deionized water until neutral, and then vacuum dry at 80°C for 12h to obtain pretreated graphite powder;
[0054] S2: pretreated graphite powder and KOH were mixed in a mass ratio of 1:3, and the mixture was placed in a nitrogen atmosphere and activated at 800°C for 1 h. After the activation, it was washed once with a 0.1 M HCl solution and then vacuum dried at 80°C to constant weight to obtain single-channel graphite;
[0055] S3: In 1M KOH electrolyte, single-channel graphite is used as the working electrode, Pt is used as the counter electrode, and saturated calomel electrode is used as the reference electrode. Constant voltage charging is performed at 2V for 2h to obtain a graphite-based basic charged adsorbent.
[0056] Comparative Example 2
[0057] This comparative example is solid waste graphite that has been pickled and expanded at high temperature;
[0058] The solid waste graphite was immersed in 6M HCl and stirred at 60°C for 2h, then the acid-washed solid waste graphite was washed with deionized water until neutral, placed in a nitrogen atmosphere, and kept at 800°C for 2.5h to obtain pretreated solid waste graphite;
[0059] The solid waste graphite-based alkaline charged adsorbents prepared in Examples 1 to 3 of the present invention have similar performance effects, and the solid waste graphite-based alkaline charged adsorbent prepared in Example 1 is used in subsequent experiments.
[0060] Experimental Example 1
[0061] Characterization experiment: The raw material (solid waste graphite) used in Example 1 and the solid waste graphite-based alkaline charged adsorbent prepared in Example 1 were analyzed using a scanning electron microscope. The SEM image of the solid waste graphite is as follows: Figure 1 As shown, the SEM image of the solid waste graphite-based alkaline charged adsorbent prepared in Example 1 is as follows Figures 2 to 4 As shown, pore sizes of different sizes correspond to macropores, mesopores and micropores, respectively, indicating that the solid waste graphite-based alkaline charged adsorbent prepared in Example 1 successfully formed a gradient pore distribution on the basis of solid waste graphite.
[0062] Experimental Example 2
[0063] Adsorption-regeneration cycle experiment: according to Figure 5 The adsorption-regeneration cycle experiment was carried out on Example 1 and Comparative Examples 1-2. The adsorption environment was 25°C and 400 ppm of CO2. The regeneration conditions of Example 1 were to apply a reverse voltage (-2 V), CO3 2 - is decomposed into CO2 and O2-, and OH- is regenerated in situ, with a regeneration energy consumption of 0.6 GJ / tCO2; the regeneration condition of comparative example 1 is Joule heating (90°C) desorption, and the regeneration energy consumption is 1.2 GJ / tCO2; the regeneration condition of comparative example 2 is traditional steam purge, and the regeneration energy consumption is 1.5 GJ / tCO2; it can be seen that the regeneration energy consumption of the present invention is low, which reduces energy consumption.
[0064] Experimental Example 3
[0065] Air carbon capture experiment: The solid waste graphite-based alkaline charged adsorbent prepared in Example 1, the graphite-based alkaline charged adsorbent prepared in Comparative Example 1 and the solid waste graphite of Comparative Example 2 were degassed at 100°C for 15 hours in vacuum to remove residual moisture and impurities, and then 400ppm CO2 was introduced at 30°C to simulate dry air adsorption, 100% N2, 100°C desorption, and the CO2 adsorption performance of the adsorbent at ultra-low concentration was tested. The experimental results are as follows Figure 6 As shown, the adsorption capacity of the solid waste graphite-based alkaline charged adsorbent prepared in Example 1 is stable at about 0.6 mmol / g, which is much better than that of Comparative Examples 1-2.
[0066] Experimental Example 4
[0067] Cycle experiment: The solid waste graphite-based alkaline charged adsorbent prepared in Example 1 was degassed at 100°C for 15 hours in vacuum to remove residual moisture and impurities, and then CO2 adsorption was performed at 25°C for 20 minutes, and CO2 desorption was performed at 100°C for 20 minutes. The cycle was repeated 100 times. The results are as follows: Figure 6 As shown, after 100 cycles, the solid waste graphite-based alkaline charged adsorbent still maintained 95% of its capacity, showing excellent stability.
[0068] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A method for preparing a solid waste graphite-based alkaline charged adsorbent, characterized in that: The following steps are involved: S1: acid-washing the solid waste graphite, then placing the acid-washed solid waste graphite in an inert gas atmosphere, keeping it at 750-850° C. for 2-3 hours, and grinding it into powder with a particle size of ≤50 μm after the end of the insulation, to obtain pretreated solid waste graphite; S2: Mix the pretreated solid waste graphite and CaCO3, add H2O2 and stir evenly to obtain a composite slurry; S3: molding the composite slurry into a film of 0.2-0.3 mm, and drying the film in vacuum at 100° C. for 24 h, and then cutting the film into graphite electrode sheets; S4: In the electrolyte, the graphite electrode sheet is used as the working electrode, Pt is used as the counter electrode, and SCE is used as the reference electrode for charging to obtain the solid waste graphite-based alkaline charged adsorbent.
2. The method for preparing the solid waste graphite-based alkaline charged adsorbent according to claim 1, characterized in that: The pickling is performed by soaking the solid waste graphite in 20% hydrochloric acid for 10 to 20 minutes.
3. The method for preparing the solid waste graphite-based alkaline charged adsorbent according to claim 1, characterized in that: The grinding is to ball-mill the solid waste graphite at a rotation speed of 300 to 500 r / min.
4. The method for preparing a solid waste graphite-based alkaline charged adsorbent according to claim 1, characterized in that: The mass ratio of the pretreated solid waste graphite to CaCO3 is 1:2-5.
5. The method for preparing the solid waste graphite-based alkaline charged adsorbent according to claim 1, characterized in that: The material ratio of the mixture of pretreated solid waste graphite and CaCO3 to H2O2 is 1g:1~3mL.
6. The method for preparing the solid waste graphite-based alkaline charged adsorbent according to claim 1, characterized in that: The electrolyte is KOH solution or NaHCO3 solution.
7. The method for preparing a solid waste graphite-based alkaline charged adsorbent according to claim 1, characterized in that: The charging is constant voltage charging for 2 h at a voltage of 2 V or pulse charging for 2 h at a voltage of 0.5 V and an interval of 10 min.
8. The solid waste graphite-based alkaline charged adsorbent obtained by the preparation method of the solid waste graphite-based alkaline charged adsorbent according to any one of claims 1 to 7.
9. Use of the solid waste graphite-based alkaline charged adsorbent according to claim 8 in air carbon capture.
Citation Information
Patent Citations
Preparation method of hierarchical porous graphene and application of hierarchical porous graphene
CN113247887A
Activated carbon with high adsorption rate and preparation method thereof
CN116328722A
Method for preparing carbon dioxide adsorbent from waste lithium battery graphite slag
CN117225367A
Modified porous amorphous carbon negative electrode material as well as preparation method and application thereof
CN118841546A
Supercapacitive swing adsorption
US20140166499A1